Linking procedural and interactional justice perceptions with organizational commitment through formation of perceived organizational support - Bálint, M.; Möhring, M. M.; Silva, J. M. V.-B. da (Proceedings of the 26th EurOMA Conference: Operations Adding Value to Society, 2019)
Building on the social exchange perspective and organizational support theory, this study aims to evaluate the relationship between truck driver’s procedural and interactional justice perceptions and their affective commitment to their employers. We set out a Transactional Justice Interaction Reference Model and refine it by scientific testing. The evidence is based on survey data collected at a truck-driving school near Frankfurt, Germany, providing update and safety classes to long-standing truck drivers in logistics and SCM. The results are derived by using structural equation modelling and indicate that perceived organizational support plays a mediating positive effect on developing organizational commitment.